Migration Analysis of West African Countries - Agubo, Onajiyoma C.; Folarin, Sheriff F (International Journal of Psychosocial Rehabilitation, 2020)
West Africa is often characterised as a model of legal and illegal forms of migration owing to several factors like over population, diverse cultures and languages, huge stock of internal migration, low income economies leading to poverty and a free movement administration strongly backed by the Economic Community of West African States(ECCOWAS). However, very little is known about the nexus between migration and the actual reasons to migrate in West Africa. Indeed, this researchwill attempt to carry out an understudy of the reasons, constraints and benefits for both origin and destination countries and how migration can help in developing the West African region. The paper concludes that constraints such as policies put in place to curb free movement can be detrimental to the stay of migrants residing in destination countries.